The Role of Entrepreneurial Motivation as A Mediator for The Campus Environment and Entrepreneurial Self-Efficacy in Generation Z - Herijanto, Beatrix Adelaide; Sitepu, Srinathasya Br (Indonesian Journal of Business and Entrepreneurship, 2025)
Background: Micro, Small, and Medium Enterprises (MSMEs) played a very important role in the national economy, including in the city of Surabaya. Generation Z, who studied at entrepreneurship-based universities, had great potential in the MSME sector through their creative and innovative character. Their success in running a business was determined not only by this potential but also by internal and external factors. A supportive campus environment, individual levels of entrepreneurial self-efficacy, and entrepreneurial motivation were important elements that directly impact the business performance.Purpose: This study aims to analyze the influence of factors that affect business success in Generation Z, consisting of entrepreneurial self-efficacy, campus environment, and entrepreneurial motivation.Design/methodology/approach: This quantitative study used primary data. The respondents of this study were Generation Z as business actors at X University in Surabaya, with a sample of 100 people taken through purposive sampling techniques using questionnaires. Data analysis was performed using SmartPLS 4.0 to determine the relationship between entrepreneurial self-efficacy, campus environment, and entrepreneurial motivation on business success.Findings/Results: The results of the study show that entrepreneurial self-efficacy and campus environment have a significant influence on entrepreneurial motivation in Generation Z as entrepreneurs, which ultimately has a positive impact on their business performance. Entrepreneurial self-efficacy and campus environment shown to not only affect entrepreneurial motivation and business performance directly but also have an indirect influence through entrepreneurial motivation as a mediating variable. This result indicates that Generation Z's business performance is significantly influenced by entrepreneurial self-efficacy, campus environment and entrepreneurial motivation.Conclusion: Generation Z involved in MSMEs will succeed if their campus environment provides adequate support. This support must also be accompanied by efforts to form entrepreneurial character and develop self-efficacy, which play an important role in increasing motivation and supporting business success.Originality/value (State of the art): This study provides new insights into the influence of the campus environment, entrepreneurial self-efficacy, and entrepreneurial motivation on the success of Generation Z businesses in the MSME sector. These findings emphasize the importance of universities in facilitating the development of student businesses, especially in building motivation and entrepreneurial character that increases success in the business world. Keywords: entrepreneurial self-efficacy, campus environment, entrepreneurial motivation, business performance, MSMEs